2020
DOI: 10.1017/s0376892920000119
|View full text |Cite
|
Sign up to set email alerts
|

Influence of experience, interest, knowledge and learning source on children’s attitudes towards extensive grassland conservation

Abstract: SummaryDecisions made by grassland owners are crucial for the conservation of extensive grasslands (EGs); however, the predispositions determining how adults decide to act in certain situations are developed during childhood. Children are future decision-makers and potential grassland owners; therefore, the factors that form and affect their attitudes towards EG conservation need to be examined. Positive attitudes could be developed during environmental education, and this study aimed to understand the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 32 publications
4
3
0
Order By: Relevance
“…In our results, the change in the behavioral intention of the students was frequently associated with the cognitive component factors and mostly the 'biology and health knowledge' factor, reinforcing the impact of our educational activity. Similar results were obtained in previous studies where the learning achieved during educational activities directly and/or indirectly influenced students' attitudes towards specific species (34)(35)(36)(37)67).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our results, the change in the behavioral intention of the students was frequently associated with the cognitive component factors and mostly the 'biology and health knowledge' factor, reinforcing the impact of our educational activity. Similar results were obtained in previous studies where the learning achieved during educational activities directly and/or indirectly influenced students' attitudes towards specific species (34)(35)(36)(37)67).…”
Section: Discussionsupporting
confidence: 90%
“…After the implementation of the activity, a significant increase in students choosing the biodiverse bag was observed. These positive results towards the conservation of intraspecific diversity after the implementation of an educational activity are similar with other studies' results on children's attitudes towards certain species such as human parasites, birds, reptiles or extensive grassland (34)(35)(36)(37). However, the percentage of students who chose the biodiverse bag in the post-test (33.33%) suggests that the approach could be improved.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some studies have shown that educational activities can have a positive impact on students’ attitudes, such as towards human parasites [ 34 ], birds [ 35 ], reptiles [ 36 ] and conservation of extensive grasslands [ 37 ]. Furthermore, a survey was administered to elementary school students showed that factors such as gender, species knowledge, preferred leisure activities, and family members’ involvement in nature protection organizations are a significant predictor of children’s attitudes toward insects [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…An effective awareness-raising strategy could be to target children living in the landscape, which could facilitate biocentric reasoning towards pangolins from a young age (i.e. promote the ideology of the intrinsic value of pangolins that is separate from their worth as a commodity; Špur et al, 2020;Kahn & Kellert, 2002). This approach could also foster protective attitudes towards pangolins among adults (Damerell et al, 2013).…”
mentioning
confidence: 99%